Stimulation Induced Electrographic Seizures in Deep Brain Stimulation of the Anterior Nucleus of the Thalamus Do Not Preclude a Subsequent Favorable Treatment Response - Nora, Tommi; Heinonen, Hanna; Tenhunen, Mirja; Rainesalo, Sirpa; Järvenpää, Soila; Lehtimäki, Kai; Peltola, Jukka (Frontiers in Neurology, 2018)
Deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT) is a method of neuromodulation used for refractory focal epilepsy. We report a patient suffering from drug-resistant epilepsy who developed novel visual symptoms and atypical seizures with the onset of ANT-DBS therapy. Rechallenge under video electroencephalography (vEEG) recording confirmed that lowering the stimulation voltage alleviated these symptoms. Subsequent stimulation with the initial voltage value did not cause the recurrence of either the visual symptoms or the new seizure type, and appeared to alleviate the patient’s seizures in long-term follow-up. We therefore hypothesize that the occurrence of stimulation induced seizures at the onset of DBS therapy should not be considered as a failure in the DBS therapy, and the possibility of a subsequent favorable response to the treatment still exists.